Fumarate hydratase-deficient renal cell carcinoma complicated with liver metastasis: case report - Chen, Hanmin; Zeng, Qingming; Liu, Folin; Zou, Xiaofeng (Frontiers in Surgery, 2024)
BackgroundFumarate hydratase-deficient renal cell carcinoma (FH-RCC) is a rare subtype of kidney tumor. Most of them are solitary lesions, making preoperative diagnosis difficult, aggressive, and with poor prognosis. They may metastasize even at an early stage, however, there is currently no optimal diagnostic and therapeutic approach for metastatic FH-RCC.MethodsWe report the case of a 34-year-old male patient with renal tumor and liver metastasis, who underwent open tumor resection of the right kidney combined with resection of liver metastases. Postoperative pathology was confirmed, followed by targeted therapy.ResultsPostoperative pathological results confirmed FH-RCC, targeted therapy was performed after surgery. No tumor recurrence was observed during the follow-up of almost 16 months.ConclusionFH-RCC patients with liver metastasis can achieve a good prognosis through early resection of primary tumor and metastatic lesions combined with targeted therapy.